Patient exposure in the basic science classroom enhances differential diagnosis formation and clinical decision-making - Peacock,Justin G.; Grande,Joseph P. (PeerJ PrePrints, 2014)
Purpose: The authors proposed that introducing real patients into a pathology classroom early in medical education would help integrate fundamental principles and disease pathology with clinical presentation and medical history. Methods: Three patients with different pathologies described their history and presentation without revealing their diagnosis. Students were required to submit a differential diagnosis in writing, and then they were able to ask questions to arrive at the correct diagnosis. Students were surveyed on the efficacy of patient-based learning. Results: Average student scores on the differential diagnosis assignments significantly improved 32% during the course. From the survey, 72% of students felt that patient encounters should be included in the pathology course next year. 74% felt that the differential diagnosis assignments helped them develop clinical decision-making skills. 73% felt that the experience helped them know what questions to ask patients. 86% felt that they obtained a better understanding of patients’ social and emotional challenges. Discussion: Having students work through the process of differential diagnosis formulation when encountering a real patient and their clinical presentation improved clinical decision-making skills and integrated fundamental concepts with disease pathology during a basic science pathology course. o
Keywords: differential diagnosis; clinical decision-making; patient exposure; undergraduate medical education; pre-clinical; pathology; basic science; history-taking; empathy; clinical skills